THE DEVELOPMENT OF ISLAMIC SCIENCES DURING THE SELJUK SULTAN SANJAR PERIOD - Abdupattaev Mumin Mirzo Murodjon (EPRA International Journal of Research and Development (IJRD), 2023)
In this article highlights of the development of islamic sciences during the seljuk Sultan Sanjar period.